Spatial-temporal conditionality of the political process in modern Russian Federation - Valeriya Vladimirovna Vikulina, Natalya Rinatovna Balynskaya, Elena Vladimirovna Karpova,; Sergey Yurievich Volkov, Elena Anatoljevna Pikalova, Alexey Grigor'ievich Pudov, Natalya Sergeevna Shkurko, (Opción, 2019)
This article focuses on the political process in Russia from the perspective of its spatial and temporal conditionality via the method of analysis and synthesis, that is, placing political events in the coordinate system. In this work, the authors use a functional approach. As a result, even concepts such as space and time, borrowing from the exact sciences and transferred into the sphere of politics, about the political process, get their realization only in the form of certain information. The authors conclude that the classical scheme in which the cause of an event entails its consequences is primarily broken today.